Nectar Feeding on an Exotic Tree ( Grevillea robusta ) by Alouatta caraya and Its Possible Role in Flower Pollination - Pavé, Romina Elizabeth (2009)
Nectar is a high-energy resource and an important food source for mammals living in habitats with marked seasonality.Black and gold howler monkeys, Alouatta caraya, are characterized by a folivore-frugivore opportunistic diet. Grevillea robusta (Family Proteaceae) is a tree native to eastern Australia and it has been widely planted in subtropical and tropical environments of Africa, America, and Asia. For exotic plants like G. robusta in forests in northeast Argentina, pollination success depend on density of plant populations which may affect the attractiveness of enough pollinators, the competition with native vegetation for pollinator attention, and the low number of suitable generalist pollinator species.The aim of this study is to describe the nectar feeding behavior of Alouatta caraya on an exotic tree (Grevillea robusta, Proteaceae) and suggest the possible role of this primate in flower pollination.